EU financial regulatory reform: a status report - Nicolas Véron (Bruegel, 2010)
In this paper, Nicolas Veron argues that the EU regulatory response to the crisis has been generally slower in the EU than in the United States, for four main reasons: swifter financial crisis management and resolution in the US; structural differences in legislative processes; the EU's front-loading of institutional reform, most notably the creation of European Supervisory Authorities; and the timetable of renewal of the European Commission in 2009-10. The EU has nevertheless initiated or completed significant regulatory initiatives in terms of banking, market structures, private equity and hedge funds, rating agencies and accounting. However, major further challenges loom.
Keywords: 330; Finanzmarkt; Regulierung; Aufsichtsbehörde; Bankenpolitik; EU-Staaten